Notional and conceptual approaches to radicalization as a process of violent extremism development - Jugovic, Aleksandar; Živaljević, Dragan (Sociološki pregled, 2021)
Radicalization is a political, social, psychological and group process that leads to the circumstances where certain political beliefs are accompanied by the readiness of an individual or a group to manifest violent extremism and acts of terrorism in a direct manner. This paper is aimed at the analysis of the concepts of radicalization, extremism and terrorism, and the classification and explanation of different concepts of radicalization. The paper applies the methods of analysis, synthesis and classification. Radicalization is classified and explained through three general approaches: structural contexts, risk factors and the development of radicalization. The key result of the paper is the conclusion about the need for the scientific development of a comprehensive theory of radicalization. The synthetic integrative theory of radicalization development should take into account different and mutually conditioned dimensions of this process.
Keywords: radicalization; violent extremism; terrorism